Zinc(II)‐Catalyzed Synthesis of Propargylamines by Coupling Aldimines and Ketimines with Alkynes. Issue 1 (3rd January 2018) - Shehzadi, Syeda Aaliya; Saeed, Aamer; Lemière, Filip; Maes, Bert U. W.; Abbaspour Tehrani, Kourosch
Abstract : A Zn II ‐catalyzed reaction between imines, which were derived from unactivated aldehydes or ketones and primary amines or α‐amino acid esters, and terminal alkynes has led to the rapid and efficient formation of tri‐ and tetrasubstituted propargylamines (from aldimines and ketimines, respectively) in good to excellent yields. No additives or extra Lewis acid reagents were required for the imine‐alkyne coupling reaction. Abstract : Imines derived from unactivated aldehydes or ketones and primary amines or α‐amino acid esters have been shown to undergo a Zn II ‐catalyzed reaction with a variety of terminal alkynes to give secondary propargylamines that have tri‐ and tetrasubstituted α‐carbon atoms (from aldimines and ketimines, respectively).